Hubungan Hukum Taurat Dan Injil - Sri Wahyuni; Rajokiaman Sinaga (STT Kingdom, 2022)
The relationship of the Law and the Gospel are two important components in the plan of salvation. The Law does not save but it can make us aware of our sinfulness which in turn leads us to the gospel, which is the saving grace of God. The Law and the Gospel both reveal to us what God is like, for from that law we know His just nature, and from the gospel we know His loving nature. Salvation can be obtained through faith, not only believing in the gospel He gave but also trusting in his given Law. The Bible states” You know, that no one is justified for doing the law, but only because of faith in Christ Jesus. Therefore we also belive in Jesus Christ, that we may be justified by faith in Christ and not by practicing in law. For: “ no one is justified’ for doing the law of Torah “ ( Gal. 2:16). The method used is a qualitative research method using various library studies and various sources. While the result of the research that the author got is that the law takes into account the truth for those who obey, but the gospel depends on the love ( his godliness ) of Christ as the truth and the righteous before God. Both the law and the Gospel are the Word of God.